NEUROMUSCULAR PERFORMANCE OF WOMEN WITH KNEE OSTEOARTHRITIS - Fernandes, Luísa Pereira [UNESP]; Navega, Marcelo Tavella [UNESP]; Spinoso, Deborah Hebling [UNESP] (Elsevier, 2024)
Background Knee osteoarthritis (KOA) is characterized by progressive degeneration of cartilage and periarticular tissue, resulting in narrowing of the joint space, formation of osteophytes and sclerosis of the subchondral bone. Compromised ability to generate muscle torque and power has been the most predominant symptom of KOA and may be related to the difficulty in performing the main activities of daily living. The muscle strength deficit in KOA affects the entire lower limb, being more pronounced in the knee extensors, 40% lower in relation to healthy individuals of the same age group. Strength together with quadriceps muscle power may be clinically more important to identify functional deficits in these patients, providing more accurate information about the neuromuscular system in relation to imaging exams. Objectives The aim of the study was to compare peak torque and rate of torque development of knee extensors in women with and without knee KOA. Methods 71 women participated in this study, divided into a group with Knee Osteoarthritis (GOAJ; n= 39) and a control group (GC; n=32). For the GOAJ, the individuals had a radiological diagnosis of tibiofemoral OA and for the CG, the individuals did not have a history of alterations related to chronic-degenerative diseases in the lower limbs. To evaluate the knee extensor torque, the volunteers performed 3 maximum voluntary isometric contractions, for a period of 5 seconds, with an interval of 30 seconds between each contraction. Torque data were normalized by the volunteers' body mass. A load cell (Noraxon®), with a sampling frequency of 100 Hz, was coupled to the lever of the leg extension chair for the acquisition of joint torque data. Peak torque was determined by the highest torque value obtained after the onset of muscle contraction, and the average of the values of the three contractions performed was calculated. To calculate the torque development rate (TDT), the slope of the torque versus time curve was analyzed, in windows of 0-30 and 0-200ms. For statistical analysis, the T test for Independent Samples was used, considering the significance level of p <0.05. Results The knee extensor torque of the GOAJ was 54% lower compared to the CG. Regarding DTT, there was a significant difference both in the initial and late phase of muscle contraction, with GOAJ presenting values, respectively, 49% and 36% lower than the CG. Conclusion Women with KOA have neuromuscular impairment in relation to women in the same age group without the disease. Implications The neuromuscular variables analyzed show that women with KOA have a lower ability to produce force and generate rapid nerve impulses in a short period, which may predispose these individuals to falls and contribute to the worsening of functional mobility in this population.